Review of The Practicality of Physics Teaching Materials on Optical Devices Material That Is Loaded With Al-Quran Verses - Edo Meidyantoro; Zainuddin Zainuddin; Surya Haryandi (Universitas Lambung Mangkurat, 2025)
This research is a Research and Development (R&D) study to obtain feasible teaching materials containing Quranic verses that provide information on practicality in learning. This study aims to determine the practicality of teaching materials based on the level of readability of teaching materials for optical devices with Al-Quran verses that were developed. This research is research and development using the ADDIE model and was tested on 42 students of class XII IPA, one of the public high schools in the Tanah Laut district. The readability questionnaire of teaching materials was used in the data collection method to evaluate readability. The data analysis method was used descriptively. The results showed that the teaching materials containing Al-Quran verses were practical regarding clarity of text and writing, appearance, ease of activities, clarity of instructions, attractiveness, and language use, so they met the practical category. The implication of this research is to help the development of physics teaching materials with Al-Quran verses that are more interesting for students, so that they can increase students' learning motivation by linking physics concepts with religious values.